The application of metrics to the measurement of quality systems - Williamson, A. (Cranfield University, 1995)
Quality system auditing has been a topic of much recent discussion but there has not been a commensurate amount of research on how the audit process can make more effective use of auditor time and improve the quality of their judgements. An approach certification bodies and their clients may adopt is to measure the quality system activities of the client, and use these measurements (or metrics) to improve their understand of the quality system. If these metrics were available to auditors, they could identify the strengths and weaknesses of the quality system and assist in deciding if the client complies with ISO 9000. This could make the audit process more cost-effective and focused. A detailed study of the current auditing process used by certification bodies, and a survey of auditors, identified the quality system activities that provide the most confidence that the company has a compliant quality system. The "quality loop" activities of internal audit/management review and corrective action were found to be both the most important activities in showing compliance and provide the basis of metrics that can inform the auditor about the state of health of these activities. Metrics capable of measuring the other quality system activities required by ISO 9000 are identified, and their effectiveness in monitoring the quality system is discussed. The research shows that metrics concerned with the quality loop can provide useful information to an auditor and can help them in reaching a judgement. It is also shown that the use of metrics is constrained by organisational and technical factors, such as the size of the organisation being measured and the correspondence between the activity being measured and the requirements of ISO 9000.